What does success mean for autistic men? A narrative exploration of self-determination. (July 2020) - Webster, Amanda A; Garvis, Susanne
Background: Studies involving autistic adults have often focused on negative outcomes and quality of life ratings. Aims: This study provides a different viewpoint by examining the perspectives of autistic men who consider themselves to be successful. Methods: Data were gathered from 10 men who shared their experiences and perceptions regarding their journey to achieve success. Self-determination theory provided a useful lens for examining the men's narratives and understanding the factors that led to their success. Results: Analysis of interviews revealed four main themes: (1) being my own self, (2) a competent professional, (3) solving problems in a neurotypical world, and (4) relating and connecting. These themes reflect the men's perception of their own self-determination including their autonomy, competence, and relatedness with others. Conclusions: The men's sense of success was derived from their ability to achieve competence in their work, act without help or influence from others and demonstrate a high level of self-awareness and self-reflection. Despite this, many continued to experience difficulty in the social areas of their lives. Implications: These findings suggest that self-determination theory may present an alternative and more positive means of enacting support programs for autistic individuals, and males in particular.